A solid state electrochemical device for studying thermodynamic and transport properties of non-stoichiometric oxides: Application to ceria - Garcia, Philippe; Steil, Marlu Cesar; Miard, Audrey; Douguet-Bronnec, Erwin; Fournet-Fayard, Franck; Fouletier, Jacques (Solid state ionics, 2021)
•Original and versatile setup for characterizing non-stoichiometric oxides using coulometric titration and EMF method.•Theoretical analysis of EMF measurement in inhomogeneous MIEC.•Out of equilibrium measurements of chemical diffusion and solid-gas exchange coefficients for ceria. An electrochemical tool for characterising properties of non-stoichiometric oxides is described that is based on Electromotive Force (E.M.F.) measurements and coulometric titration. The tool may be used to subject samples to either solid-state or gas phase redox perturbations. A theoretical analysis of the setup shows that the open-circuit voltage (OCV) is characteristic of the oxygen activity in the solid at the interface between the sample and the Yttria Stabilised Zirconia (YSZ) sample-holder in the case of an inhomogeneous, essentially electronic conducting material. The device's purpose is illustrated with a study of cerium oxide at 900°C. By running simple solid state reduction experiments, it is possible to simultaneously derive thermodynamic and chemical diffusion data consistent with existing literature. The approach we present appears as an interesting alternative to other techniques such as the relaxation method or impedance spectroscopy.